2017
DOI: 10.1002/anie.201610778
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of Membrane Proteins into Functional Lipid‐Bilayer Nanodiscs Using a Diisobutylene/Maleic Acid Copolymer

Abstract: Once removed from their natural environment, membrane proteins depend on membrane‐mimetic systems to retain their native structures and functions. To this end, lipid‐bilayer nanodiscs that are bounded by scaffold proteins or amphiphilic polymers such as styrene/maleic acid (SMA) copolymers have been introduced as alternatives to detergent micelles and liposomes for in vitro membrane‐protein research. Herein, we show that an alternating diisobutylene/maleic acid (DIBMA) copolymer shows equal performance to SMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
337
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(365 citation statements)
references
References 30 publications
(62 reference statements)
22
337
0
1
Order By: Relevance
“…2a). Since SMA(3:1) has been found518 to lower the gel-to-fluid transition temperature of DMPC, the lipid bilayers in the SMALP core were always in the fluid state, as confirmed calorimetrically (Supplementary Fig. 1).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…2a). Since SMA(3:1) has been found518 to lower the gel-to-fluid transition temperature of DMPC, the lipid bilayers in the SMALP core were always in the fluid state, as confirmed calorimetrically (Supplementary Fig. 1).…”
Section: Resultssupporting
confidence: 57%
“…Owing to their small size, SMALPs are well suited for optical-spectroscopic13489121415 and chromatographic13151617 techniques. Likewise, a diisobutylene/maleic acid (DIBMA) copolymer has been found18 to solubilise membrane proteins and lipids in a mild fashion, that is, without major perturbation of the bilayer order in DIBMA/lipid particles (DIBMALPs).…”
mentioning
confidence: 99%
“…The amphiphilic belt is critical for the stability and function of nanodiscs. Studies have reported different types of surrounding belts including Membrane Scaffold proteins (MSPs) [5, 7] , peptides [8] , and polymer [9] . Even though MSP-based nanodiscs are excellent mimics of the membrane, the reconstitution of a membrane protein still requires the undesirable use of detergents [10] , and therefore detergent-free solubilization of membrane proteins attracted new attention in the field [11, 12] .…”
mentioning
confidence: 99%
“…Due to their large sizes, liposomes exhibit completely broadened phosphorus-31 NMR signals, while rapidly tumbling nanodiscs yield sharp signals for contained phospholipids. The transition is sharp, moving rapidly from onset to completion of membrane solubilization with only a neglible concentration of free polymer DIBMA [23]. The proton NMR spectra of the polymer and contained proteins are broadened due to the polydispersity of the polymers and heterogeneity of the assemblies [1].…”
Section: Composition Of Polymer-lipid Particlesmentioning
confidence: 99%
“…An alternative to SMA polymers with aliphatic rather than aromatic moieties was recently found by Sandro Keller and colleagues [23] to more gently extract membrane proteins. It offers alternating diisobutylene and maleic acid sidechains that are less perturbing to native naodiscs and hence may be advantageous for solubilizing particularly labile protein complexes.…”
Section: Introduction To Polymer-based Membrane Solubilizationmentioning
confidence: 99%